Human Resource Management in the Public Sector in Relation to the Political Orientation of Papuan Ethnic Groups During the 2024 Legislative Elections in Sorong City, Southwest Papua Province - Kondjol, Ariance Sara (KnE Social Sciences, 2025)
The 2024 legislative elections in Sorong City, Southwest Papua Province, reveal significant dynamics in the political orientation of Papuan ethnic groups. This study analyzes how human resource management (HRM) practices in the public sector influence and are influenced by ethnic identity politics during the election process. Employing a qualitative approach, the research involved in-depth interviews with 15 participants, including local government officials, community leaders, and political party representatives. It examines how recruitment, placement, and promotion of public officials are shaped by ethnic affiliations and political interests. The findings indicate that public sector HRM, which ideally should prioritize meritocracy and professionalism, is often compromised by ethnic considerations, leading to challenges in governance, service delivery, and public trust. Strengthening inclusive, competency-based human resource management practices is essential to ensure fair representation and improve governance quality in Sorong City. This study contributes to the broader understanding of ethnicity, public sector management, and electoral dynamics in multicultural societies.